2007
DOI: 10.1002/ijc.22568
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel single nucleotide polymorphism in the first tandem repeat sequence of the thymidylate synthase 2R allele

Abstract: Thymidylate synthase (TS) activity is an important determinant of response to chemotherapy with fluoropyrimidine prodrugs and its expression is largely determined by the number of functional upstream stimulatory factor (USF) E-box consensus elements present in the 5 0 regulatory region of the TYMS gene. Two known polymorphisms in this area, a variable number of tandem repeat (VNTR) consisting of 2 or 3 repeats (2R/3R) of a 28-bp sequence and a further G > C single nucleotide substitution within the second repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…The polymorphism (G4C) in 5 0 -UTR region changes a crucial residue in the upstream stimulatory factor (USF) E-box consensus elements, abolish this USF binding and alter transcriptional activity. The classification of TYMS allele was based on the number of functional USF, consensus elements, in this 5 polymorphic region (Lincz et al, 2007). In our study, the most frequent allele was two and three USF sites (63 and 30%, respectively), whereas one or four USF sites were founded in only 2.7 and 4% of the patients, respectively.…”
Section: Genotypingmentioning
confidence: 55%
See 1 more Smart Citation
“…The polymorphism (G4C) in 5 0 -UTR region changes a crucial residue in the upstream stimulatory factor (USF) E-box consensus elements, abolish this USF binding and alter transcriptional activity. The classification of TYMS allele was based on the number of functional USF, consensus elements, in this 5 polymorphic region (Lincz et al, 2007). In our study, the most frequent allele was two and three USF sites (63 and 30%, respectively), whereas one or four USF sites were founded in only 2.7 and 4% of the patients, respectively.…”
Section: Genotypingmentioning
confidence: 55%
“…The number of 28-bp tandem repeats (2R or 3R) in the TYMS gene and the associated G4C SNP was performed as previously described (Kawakami and Watanabe, 2003;Mandola et al, 2003;Lincz et al, 2007). The polymorphism (G4C) in 5 0 -UTR region changes a crucial residue in the upstream stimulatory factor (USF) E-box consensus elements, abolish this USF binding and alter transcriptional activity.…”
Section: Genotypingmentioning
confidence: 99%
“…The need to look for more genetic variations and study them in concert has been identified. The recent discovery by us 1 and Gusella et al 2 of a new SNP in the TYMS promoter is an example of progress in this field.…”
mentioning
confidence: 99%
“…To avoid confusion, we feel the only solution is to indicate the actual nucleotide present at the 12th position of each repeat, prefixed by the number of repeats present in the allele; thus the latter most recently described 2R variant would be indicated by 2RCC. 1 Presently, the functional consequences of these polymorphisms can only be postulated based on the number of potential upstream stimulatory factor (USF) binding sites (i.e., those containing a G at the polymorphic site) in each allele. The actual effect of these repeats on gene transcription has only been specifically addressed in three reports.…”
mentioning
confidence: 99%
“…
Dear Sir, Gusella et al 1 and Lincz et al 2 have recently identified a new single nucleotide polymorphism in the enhancer region of the 2R allele of the thymidylate synthase gene (TYMS), consisting in a G>C base change at the 12th nucleotide of the first 28-bp repeat. This finding enlarges the number of possible TYMS allelic variants and calls for a revision of the present classification.
…”
mentioning
confidence: 99%